Elucidation of the paratope of scFv-8H9D4, a PAI-1 neutralizing antibody derivative - Verbeke, Koen; Gils, Ann; Stassen, Jean-Marie; Declerck, Paul J. (Thrombosis and Haemostasis, 2003)
Interfering with increased levels of plasminogen activator inhibitor-1 (PAI-1) might offer new therapeutic strategies for a variety of cardiovascular diseases. Inactivation of PAI-1 can be accomplished by a number of monoclonal antibodies (MA), including MA-8H9D4. In a previous study, a single-chain variable fragment (scFv-8H9D4) was cloned and found to have the same properties as the parental MA-8H9D4. In the present study, we identified the residues of scFv-8H9D4 that contribute significantly to the paratope. The complementarity determining region 3 from the heavy (H3) and the light (L3) chain were analysed through site-directed mutagenesis. Out of twelve mutations, only four residues appeared to contribute to the paratope. The affinity of scFv-8H9D4-H3-L97D for PAI-1 was 38-fold decreased (KA = 4.8 ± 0.2 × 107 M–1vs. 1.8 ± 0.7 × 109 M–1 for scFv-8H9D4) whereas scFv-8H9D4-H3-R98Y did not bind to PAI-1. The affinities of scFv-8H9D4-L3-Y91S and scFv-8H9D4-L3-F94D for PAI-1 were 9- and 5-fold reduced, respectively, whereas the combined mutation resulted in an 86-fold decreased affinity (KA = 2.1 ± 0.2 × 107 M–1).In accordance with the affinity data, these mutants had no, or a reduced, PAI-1 inhibitory capacity, confirming that these four particular residues form the major interaction site of scFv-8H9D4 with PAI-1. In combination with the three-dimensional structure, these data contribute to the rational design of PAI-1 neutralizing compounds.
Keywords: PAI-1; PAI-1 inhibitor; antibody; scFv; paratope